Assessing the Impact of Current Ratio, Return On Assets, and Debt To Equity Ratio on Financial Distress of PT Jasa Marga (Persero) Tbk Over the 2013-2022 - Listri Herlina; Ilham Nugroho (FEB-Telkom University Publisher, 2024)
This study aims to examine the Financial Distress of PT Jasa Marga (Persero) Tbk through its financial performance. The analysis explores into the challenges associated with infrastructure development, particularly toll roads, wherein the high levels of financing and capital requirements lead to a significant increase in corporate debt. If it is not managed properly, this could potentially result in bankruptcy for the company. Using the Ordinary Least Square (OLS) method to analyze the issue, three internal factor variables were employed: Current Ratio (CR), Return On Assets (ROA), and Debt To Equity Ratio (DER).Based on the research findings, PT Jasa Marga (Persero) Tbk experienced financial distress from the second quarter of 2020 to the second quarter of 2021. Return on Assets (ROA) and Debt to Equity Ratio (DER) emerged as the primary factors influencing financial distress, whereas Current Ratio (CR) had no significant impact on it. With the influence of ROA and DER, PT Jasa Marga (Persero) Tbk faces a high risk concerning its ability to repay debts, attract new investments, or maintain a healthy financial balance. This could lead to a decline in the company's value, difficulties in accessing new sources of funding, or even bankruptcy. PT Jasa Marga (Persero) Tbk must consistently strive to improve its financial performance with careful attention.Keyword: Financial Distress; Current Ratio; Return on Assets; Debt to Equity Ratio; Ordinary Least Square (OLS).